Penilaian Kesamaan Entity Relationship Diagram dengan Algoritme Tree Edit Distance - Humasak Simanjuntak; Rosni Lumbantoruan; Wiwin Banjarnahor; Erisha Sitorus; Magdalena Panjaitan; Sintong Panjaitan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Main competency in database learning is ability to design Entity Relationship Diagram (ERD). Generally, lecturer gives task to students to design an ERD with some requirements. These ERDs are then assessed by comparing them with the answers. In practice, the process takes long time and it is possible that the lecturer grades the students inconsistently. Furthermore, plagiarism could be occured without being noticed by the lecturer. This research aims to design and build an application that assess similarity of ERD. The application apply tree edit distance algorithm in checking ERD similarity. ERD is exported into XMI document and then processed using the tree edit distance algorithm. The results show that ERD similarity value depends on number of insert, delete, and rename operation in tree edit distance Algorithm rather than number of difference component.